Predicting the past: Understanding the causes of bank distress in the Netherlands in the 1920s - Christopher L. Colvin; Abe de Jong; Philip T. Fliers (Queen's University Centre for Economic History (QUCEH), 2014)
Why do some banks fail in financial crises while others survive? This article answers this question by analysing the effect of the Dutch financial crisis of the 1920s on 142 banks, of which 33 failed. We find that choices of balance sheet composition and product market strategy made in the lead-up to the crisis had a significant impact on banks' subsequent chances of experiencing distress. We document that high-risk banks - those operating highly-leveraged portfolios and attracting large quantities of deposits - were more likely to fail. Branching and international activities also increased banks default probabilities. We measure the effects of board interlocks, which have been characterized in the extant literature as contributing to the Dutch crisis. We find that boards mattered: failing banks had smaller boards, shared directors with smaller and very profitable banks and had a lower concentration of interlocking directorates in non-financial firms.
Keywords: G01; G21; G33; G34; N24; 330; financial crises; bank failures; bank business models; interlocking directorates; the Netherlands; the interwar period